Positive Fecal Occult Blood Test is a Predictive Factor for Gastrointestinal Bleeding after Capsule Endoscopy in Patients with Unexplained Iron Deficiency Anemia: A Korean Multicenter CAPENTRY Study - Ji Young Chang; Chang Mo Moon; Ki-Nam Shim; Dae Young Cheung; Hyun Seok Lee; Yun Jeong Lim; Seong Ran Jeon; Soo Jung Park; Kyeong Ok Kim; Hyun Joo Song; Hyun Joo Jang; Ji Hyun Kim (Korean Society of Gastrointestinal Endoscopy, 2020)
Background/Aims Capsule endoscopy (CE) is recommended as the primary method for the evaluation of unexplained anemia. This study aimed to assess the diagnostic yield of CE in patients with unexplained iron deficiency anemia (IDA) without overt bleeding, and to evaluate their long-term outcomes and related clinical factors. Methods Data of patients who underwent CE for the evaluation of IDA were reviewed from a CE registry in Korea. Additional clinical data were collected by the involved investigators of each hospital through a review of medical records. Results Among a total of 144 patients, the diagnostic yield of CE was 34%. Gastrointestinal (GI) bleeding was found in 6.3% (n=9) of the patients (occult bleeding in four patients and overt bleeding in five patients) during a mean follow-up of 17.8 months. Patients with a positive fecal occult blood test (FOBT) result at the initial diagnosis had a higher rate of GI bleeding after CE (p=0.004). In addition, a positive FOBT result was the only independent predictive factor for GI bleeding (hazard ratio, 5.30; 95% confidence interval, 1.41-19.85; p=0.013). Conclusions Positive FOBT is a predictive factor for GI bleeding during follow-up after CE in patients with unexplained IDA without overt bleeding. Thus, patients with positive FOBT need to be more closely followed up.